Red Giant - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2021)
In 2012, we published a paper in the Journal of Critical Globalization Studies titled 'Imperialism and Financialism: The Story of a Nexus'. Our topic was the chameleon-like Marxist notion of imperialism and how its different theories related to finance. Here is the article's summary: Over the past century, the nexus of imperialism and financialism has become a major axis of Marxist theory and praxis. Many Marxists consider this nexus to be a prime cause of our worldly ills, but the historical role they ascribe to it has changed dramatically over time. The key change concerns the nature and direction of surplus and liquidity flows. The first incarnation of the nexus, articulated at the turn of the twentieth century, explained the imperialist scramble for colonies to which finance capital could export its excessive surplus. The next version posited a neo-imperial world of monopoly capitalism where the core's surplus is absorbed domestically, sucked into a black hole of military spending and financial intermediation. The third script postulated a World System where surplus is imported from the dependent periphery into the financial core. And the most recent edition explains the hollowing out of the U.S. core, a red giant that has already burned much of its own productive fuel and is now trying to financialize the rest of the world in order to use the system's external liquidity. The paper outlines this chameleon-like transformation, assesses what is left of the nexus and asks whether it is worth keeping. (p. 42) In the second part of the paper, we looked a little closer at the red-giant argument. Specifically, we wanted to gauge the degree to which U.S. capital had declined and examine whether this decline indeed forced the rest of the world to financialize. And what we found surprised us: the 'financial sector' did seem to become more important everywhere, but its rise was led not by the United States, but by the rest of the world! Our article was published almost a decade ago, so we though it would be interesting to update our figures and see what has changed, if anything.
Keywords: P16; P26; P48; G3; F5; G1; 330; globalization; imperialism; financialization; United States